ART AT THE POINT OF SALE: ITS COMMUNICATIVE POTENTIAL AND FOUR DIFFERENT POSSIBILITIES OF APPLICATION - Bellido-Pérez, Elena (IROCAMM - International Review Of Communication And Marketing Mix, 2019)
In this text, the potential of art for retail stores is explored. No matter what product or service the store is offering than the art can always be an effective tool for pursuing certain communication goals. Being one of the most ancient communication forms, art is a wide field in which emotion plays a key role. That is why the retail sector can take advantage of the proved effectiveness of art while transferring its suggested feeling to the spatial management of the store. Thus, in this study, four different possibilities of artistic decoration in stores are described: (1) the retail management as an artistic activity, (2) the retail store as a museum space, (3) the retail store and the (integrated or recreated) artworks, and (4) the retail store and the artistic movements.